PENILAIAN TINGKAT KESEHATAN KOPERASI JASA KEUANGAN SYARIAH WANITA - Indriani, Astiwi; Fitria, Shoimatul (P4M STIE Putra Bangsa, 2020)
This study is a study of the application of the assessment of banking health level then adopted to measure the health level of Koperasi Jasa Keuangan Syariah (KJKS) for women in Central Java. The population in this study is all financial service cooperatives in Central Java in 2012-2014. The sampling technique used was purposive sampling with a sample of 5 KJKS for women. Data obtained through secondary data in the form of RAT reports and annual reports. The analysis technique used is descriptive analysis. The results of the analysis showed that the KJKS for Women in Central Java had a composite rating of 3 (PK-3), which means that each KJKS for Women in Central Java was healthy enough and able to deal with the negative effects of changes in business conditions and other external factors.